Differences of Recovery from Rocuronium-induced Deep Paralysis in Response to Small Doses of Sugammadex between Elderly and Nonelderly Patients. (November 2018) - Muramatsu, Takahiro; Isono, Shiroh; Ishikawa, Teruhiko; Nozaki-Taguchi, Natsuko; Okazaki, Junko; Kitamura, Yuji; Murakami, Noriko; Sato, Yasunori
Editor's Perspective: What We Already Know about This Topic: Sugammadex may be the best available drug to reverse residual neuromuscular blockade produced by rocuronium and vecuronium A 5% incidence of residual neuromuscular blockade has been reported after administering sugammadex without neuromuscular monitoring Elderly patients have been reported to respond differently than nonelderly patients do to rocuronium and sugammadex What This Article Tells Us That Is New: The train-of-four ratio recovery rate after low-dose sugammadex administration was slower in elderly patients than it was in nonelderly patients Recurarization after low-dose sugammadex administration occurred more frequently in elderly patients than in nonelderly patients Slower spontaneous train-of-four ratio recovery and impaired renal function were most closely associated with the decreased train-of-four ratio change rate in response to low-dose sugammadex in multiple linear regression analysis Background: Complete recovery from rocuronium-induced muscle paralysis with sugammadex is reported to be delayed in elderly patients. The authors tested a hypothesis that recovery from deep neuromuscular block with low-dose sugammadex is slower (primary hypothesis) and incidence of recurarization is higher (secondary hypothesis) in elderly patients than in nonelderly patients. Methods: In anesthetized elderly (n = 20; 76.9 ± 5.0 yr of age) and nonelderly patients (n = 20; 53.7 ± 12.8 yr of age) under deep paralysis with rocuronium, change of train-of-four ratio per minute (primary outcome variable) was measured with an acceleromyograph neuromuscular monitor during spontaneous recovery from rocuronium-induced muscle paralysis (0.6 mg/kg) and after infusion of low-dose sugammadex (50 µg · kg -1 · min -1 ). Recurarization was defined as the negative change of train-of-four ratio. Results: Spontaneous train-of-four ratio recovery rate was significantly slower in the elderly group (median [25th percentile, 75th percentile]: 1.89 [1.22, 2.90] %/min) than in the nonelderly group (3.45 [1.96, 4.25] %/min, P = 0.024). Train-of-four ratio change rate in response to low-dose sugammadex was significantly slower in elderly (0.55 [–0.29, 1.54] %/min) than in the nonelderly group (1.68 [0.73, 3.13] %/min, P = 0.024). Incidence of recurarization was significantly higher in the elderly group than in the nonelderly group (35% vs . 5%, P = 0.044). Multiple linear regression analyses indicate that slower spontaneous train-of-four ratio recovery rate and impaired renal function are two major contributing factors that decrease train-of-four ratio change rate in response to low-dose sugammadex. Conclusions: Elderly patients are at greater risk for recurarization and residual muscle paralysis when low-dose sugammadex is administered. Abstract : The train-of-four ratio recovery rate after low-dose sugammadex administration was slower in elderly patients than it was in nonelderly patients. Recurarization after low-dose sugammadex administration occurred more frequently in elderly patients than in nonelderly patients. Slower spontaneous train-of-four ratio recovery and impaired renal function were most closely associated with the decreased train-of-four ratio change rate in response to low-dose sugammadex in multiple linear regression analysis.